1996
DOI: 10.1023/a:1016007601794
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: (a) A significant cerebrovascular permeability to intact DA is mediated by a MAO-B independent specific transport system at the BBB, (b) this system could be inhibited by D1 and D2 DA receptor antagonists, and (c) DA blood-to-brain transport was inhibited by nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It has been reported that the increased level of dopamine in blood (hyperdopaminemia) could be caused by long‐lasting, obsessive eating of bananas by the patients who suffer from anorexia nervosa [] resulted in psychological changes. Though, it is generally believed that circulating dopamine do not penetrate blood–brain barrier, in long‐term arterial infusion studies, a saturable dopamine influx into brain was demonstrated []. Determination of dopamine in banana could be interesting from both dietary and biomedical point of views.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the increased level of dopamine in blood (hyperdopaminemia) could be caused by long‐lasting, obsessive eating of bananas by the patients who suffer from anorexia nervosa [] resulted in psychological changes. Though, it is generally believed that circulating dopamine do not penetrate blood–brain barrier, in long‐term arterial infusion studies, a saturable dopamine influx into brain was demonstrated []. Determination of dopamine in banana could be interesting from both dietary and biomedical point of views.…”
Section: Introductionmentioning
confidence: 99%
“…2‐(3,4‐Dihydroxyphenyl)ethylamine (dopamine) is an important neurotransmitter involved in motor and cognitive functions [], and plays a significant role in cardiovascular, renal, and hormonal systems even at very low concentration []. In the present work, dopamine was selected as the target analyte, 2‐(3,4‐dimethoxyphenyl)ethylamine imprinted polymer (MIP pt ) as the sorbent, and banana fruits as a real sample.…”
Section: Introductionmentioning
confidence: 99%